Corporate Social Responsibility & Development: A Knot of Disempowerment - Luis Eslava (Sortuz)
This paper presents a discursive analysis of the arrival, operation, and effects of Corporate Social Responsibility (CSR) on international development from a socio-legal perspective. CSR has become a priority on the international development agenda as frameworks for development promote the contraction of the state's role and seek to encourage corporate participation in addressing social issues. It is argued here, however, that CSR discourse represents an expansion of development as an antipolitics machine. As a discourse, CSR possesses a powerful capacity for selfperpetuation, allowing it to appropriate and rephrase social dissent in its own terms, and cancelling genuine political contestation. Through institutionalization, regularization and managerial capture, CSR exemplifies how discursive practices and structures embody a constellation of power relations that constrain action and obscure the intrinsically political nature of development.